THE CONSIGNMENT CONTRACT FROM THE PERSPECTIVES OF THE OLD AND NEW LEGISLATION - DAN-ALEXANDRU SITARU (Challenges of the Knowledge Society)
A form of intermediation contracts based on the mandate without representation is also the consignment agreement, a variety of the contract of commission. The consignment contract is lawfully established by Law No. 178/1934 for the regulation of the consignment contract. The New Civil Code, under Article 2054, limits to providing that this agreement is a variety of the contract of commission having as object the sale of some immovable goods which the consignor entrusted to the consignee for this purpose. The consignment agreement may be defined as the consent, by which a party, called consignor, entrusts the other party, called consignee, certain goods in view of being sold in its own name, but on behalf of the consignor, at a price established by the parties, in exchange for a payment. The consignee is bound to deliver the obtained price or, as the case may be, return the unsold good. The purpose of the paper is to underline the changes in legislation subsequently to the New Civil Code and to compare both perspectives.